The effectiveness of acid-tolerant antagonists in the control of oil palm basal stem rot disease caused by Ganoderma sp. in peat soils (Asian Journal of Agriculture, 2024)
Abstract. Supriyanto, Purwanto, Poromarto SH, Supyani. 2024. The effectiveness of acid-tolerant antagonists in the control of oil palm basal stem rot disease caused by Ganoderma sp. in peat soils. Asian J Agric 8: 143-152. Oil palm is one of the main contributors to global vegetable oil production. Some of the oil palm plantation areas are on peatlands. A serious problem of oil palm plantations in peatlands is the high incidence of Basal Stem Rot (BSR) disease caused by Ganoderma sp. Effective methods to control the oil palm BSR disease in peatlands have not been found. Biological control is an alternative control method that is currently the focus of development, however, the characteristics of tropical peatlands with ultra-low pH levels are an obstacle to its development. This research aimed to find the effective use of indigenous acid-tolerant antagonists and the effect of peat pH in the biological control of BSR disease in oil palm seedlings in peat soils. Research has been carried out in an experimental garden involving three fungi and two bacterial acid-tolerant antagonists from peatlands. The results showed that the effectiveness of acid-tolerant antagonists was 56.25% in reducing the symptoms of the disease. The difference in peat pH did not affect the effectiveness of control in hemic peat soil, however, it affected the effectiveness of disease control in sapric peat soil. This study indicates that acid-tolerant antagonists from West Kalimantan peatlands can potentially be used as biological control agents of Ganoderma in oil palms on peatlands.
Keywords: Acid-tolerant, antagonist, Ganoderma sp., oil palm, peatlands